(3jhGbjJ GdehGbjJ (B((3aj eOM GdTF hPeg(B)s - (3CHj efUhQ YHO Gdedc Hf eMeO Hf ESeGYjd GdKYGdHj,J (B429 (3g` s ((3eMeO Hf YdGA GdOjf GdJhbGfj s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPG JYdjb jTJed Ydi PcQ GdCNHGQ GdeCKhQI hGdCTYGQ GdeQhjI s
(3BNQgG (B:s
(3hcGf YeQ Hf YHOGdYRjR QMeI Gddg Ydjg dG jcGO jhLH TjFkG JhbjkG ddNda s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B187 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2535) s
Keywords: (3GdCOHs